Trust Model Development for Cloud Environment using Fuzzy Mamdani and Simulators (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Nowadays, Cloud computing is an expanding area in research and industry, which involves virtualization, distributed computing, internet, software, security, web services and etc. A cloud consists of several elements such as clients, data centers and distributed servers, internet and it includes fault tolerance, high availability, effectiveness, scalability, flexibility, reduced overhead for users, reduced cost of ownership, on demand services and etc. Now the next factor is coming, cost of Virtual machines on Data centers and response time. So this paper develop trust model in cloud computing based on fuzzy logic, to explores the coordination between Data Centers and user bound to optimize the application performance, cost of Virtual machines on Data centers and response time using Cloud Computing Analyst.